2013
DOI: 10.5194/cp-9-1455-2013
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary estimation of Lake El'gygytgyn water balance and sediment income

Abstract: Modern process studies of the hydrologic balance of Lake El'gygytgyn, central Chukotka, and the sediment income from the catchment were carried out during a field campaign in spring and summer 2003. Despite high uncertainties due to the limited data, the results provide important first estimates for better understanding the modern and past sedimentation processes in this basin. Formed ca. 3.6 million years ago as a result of a meteorite impact, the basin contains one of the longest paleoclimate records in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(48 citation statements)
references
References 19 publications
3
45
0
Order By: Relevance
“…In the deep lake basin, the accumulated sediments are fine grained Wennrich et al, 2013a), suggesting that the coarser grained mass movements, in particular debrites, but also grain flows and turbidites, originate from shallow water depths, where such sediments are found (Juschus et al, 2011). The large alluvial fan and its subaqueous prologation in the western and northern lake catchment provide coarser grained sediments into the lake basin (Schwamborn et al, 2012;Fedorov et al, 2013) and delta collapses account for some of the mass movements encountered at the lake center. This can also be seen as multiple mass flows on the western lake slope in the seismic profile (Fig.…”
Section: Possible Triggering Mechanisms For Mass Movement Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the deep lake basin, the accumulated sediments are fine grained Wennrich et al, 2013a), suggesting that the coarser grained mass movements, in particular debrites, but also grain flows and turbidites, originate from shallow water depths, where such sediments are found (Juschus et al, 2011). The large alluvial fan and its subaqueous prologation in the western and northern lake catchment provide coarser grained sediments into the lake basin (Schwamborn et al, 2012;Fedorov et al, 2013) and delta collapses account for some of the mass movements encountered at the lake center. This can also be seen as multiple mass flows on the western lake slope in the seismic profile (Fig.…”
Section: Possible Triggering Mechanisms For Mass Movement Eventsmentioning
confidence: 99%
“…Sediment is transported to the lake through fluvial and aeolian transport as well as by gravitative mass movement processes Fedorov et al, 2013;. Even though the number of inlet streams is high, their sediment discharge to the lake is rather small.…”
Section: Prerequisite Site Informationmentioning
confidence: 99%
“…1; Nolan and Brigham-Grette, 2007), which deliver sediment in the order of ca. 350 t yr −1 into the lake (Fedorov et al, 2013). In 2003, main sediment discharge occurred during snowmelt in spring and early summer, with highest values of 24 g s −1 in June and 0.33 g s −1 in August measured in creek 49 (cf.…”
Section: Site Informationmentioning
confidence: 99%
“…Our grain-size investigations on ICDP core 5011-1 extend the results from this early research to the entire Quaternary. Furthermore, we incorporated more recent findings on the modern climatological, hydrological, and sedimentological settings (Fedorov et al, 2013;Wennrich et al, 2013a). To better understand the sedimentological processes operating in Lake El'gygytgyn, we used principal component analysis (PCA) to detect dominating variations in the grain-size distributions, and we employed time series analysis to reveal oscillations in the granulometric data and their relative dominance over time.…”
Section: A Francke Et Al: Multivariate Statistic and Time Series Anmentioning
confidence: 99%
“…Earlier it was stated that the lake is snowmelt fed (Cremer and Wagner, 2003) based on the low lake water EC (< 20 µS cm −1 ). In recent studies it was found that the lake water column is well mixed with low evaporation (Chapligin et al, 2012a) and the period of lake water residence time is about 100 years (Fedorov et al, 2013). An isotopic composition similar to what has been described for snow and lake water is found in particular in HZ 4 with their matching mean δ values (Fig.…”
Section: Ground-ice Origin: Constraints From Downcore Hydrochemical Amentioning
confidence: 99%